Spatio-temporal Trend Analysis of Rainfall using R Software and ArcGIS A Case Study of an Agro-climatic Zone-1 of Gujarat, India - Naveena, K.; Tasiya, Ramiz; Rana, Shilpesh (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book aims to provide an advanced R software approach that can carry out rainfall trend analysis using Mann-Kendall and Sen's slope estimator tests. The research study follows a systematic approach while utilizing R software as it can greatly facilitate the analysis of rainfall trends. About 30 stations located in the study area and 41 to 50 years' time series were selected for the purpose of analysis. The data for the research was collected from the State Water Data Centre (SWDC) in Gujarat, Indian Meteorological Department (IMD) in Pune, DAAC (NASA), and ESRI. Cluster analysis has been performed to analyze the variability of the mean rainfall. The stations have been divided into 2 clusters with 17 and 13 stations in each cluster which significantly differ from each other. This book is aimed at researchers, scientists and government organizations working in the field of climate change. .
Chapter 1. Introduction -- Chapter 2. Literature survey -- Chapter 3. Study area and data collection -- Chapter 4. Methodology -- Chapter 5. Computations -- Chapter 6. Results and discussion -- Chapter 7. Conclusion. .
Keywords: Climatology; Earth sciences; Geography; Environmental engineering; Biotechnology; Bioremediation; Technical education; Climate Sciences; Earth and Environmental Sciences; Environmental Engineering/Biotechnology.; Engineering and Technology Education; Geography